UPAYA INDONESIA MENANGANI PENGUNGSI ROHINGYA DI ACEH TAHUN 2009-2015 - M. Kholit Juani (HI 15 UMY 447, 2015)
*447 This research aims to determine what efforts undertaken by Indonesia in dealing with the Rohingya refugees in Aceh. The method used in this research is descriptive analytic method. Data collection techniques gathered from secondary data from books, the internet, journals, articles, written reports, magazines, and other documents were analyzed qualitatively. The results showed that, in his arrival in Indonesia, the Rohingya refugees spread across several regions in Indonesia. Some of them exist in Indonesia as captured by the Indonesian government and some are deliberately surrendered to the Indonesian immigration whose territory close to Malaysia and Myanmar as in Aceh, Medan, Rbatam (Riau Islands), Tanjung Pinang, and some are arrested and found Area NTT (Kupang), Banten, and Banyuwangi. The reason they surrendered to the Indonesian immigration because of the condition of the Rohingya refugees in a state of starvation, they hope to give themselves will get food from the Indonesian immigration authorities. However, some of those who came to Indonesia in order to get protection with safer conditions and get a better life. In addressing the Rohingya refugees who were in Aceh, Indonesia. The Indonesian government will make policies and new legislation on refugees and asylum seekers are more complete. In addition, the Government of Indonesia and based on a sense of "humanity" to accommodate the displaced Rohingya in several regions in Indonesia with a certain time limit. Furthermore, the government in collaboration with the international community to work together to solve the problems of the Rohingya refugees proficiency level. Key Words: Indonesian Government, Rohingya Refugees.Vienna Convention.